What are the Key Characteristics of a ‘Good’ Psychotherapy? Calling for Ethical Patient Involvement - Gerger, Heike; Nascimento, Antje Frey; Locher, Cosima; Gaab, Jens; Trachsel, Manuel (Frontiers in Psychiatry, 2020)
Objective: The evidence-based practice movement clearly defines the relevant components of a good treatment. In the present article, we elaborate on how the active involvement of patients within psychotherapy can and should be increased in order to respect ethical considerations. Our arguments complement the requirements of evidence-based practice, and are independent of the actual psychotherapeutic treatment approach being used. Method: Theoretical and ethical analysis. Results: In order to respect patient autonomy, psychotherapy needs to be transparent and honest when it comes to disclosing the relevant factors for promoting therapeutic change. It has been argued that ethical informed consent needs to include empirically supported patient information. In this paper we go one step further: we outline that fully respecting ethical considerations in psychotherapeutic treatment, necessarily calls for acknowledging and strengthening the active role of patients in the course of psychotherapy. Accordingly, patients need not only to be informed openly and transparently about the planned treatment, the treatment rationale, and the expected prognosis of improvement in the course of psychotherapy, but they also need to be actively involved in the decision-making process and during the entire process of psychotherapeutic treatment. Conclusions: Our arguments support the tendency that can be observed in health care in recent years towards more active patient involvement across different health-care domains, but also in clinical research. This article offers an ethical perspective on the question what defines a ‘good psychotherapy', which, hopefully, will help to leave behind some of the ongoing psychotherapy debates and move the field forward.